The Substitutability between Brick-and-Mortar Stores and e-Commerce - The Case of Books - Georg Goetz; Daniel Herold; Phil-Adrian Klotz; Jan Thomas Schäfer (Philipps-University Marburg, School of Business and Economics, 2020)
We analyze the substitutability between brick-and-mortar stores and e-Commerce. Using a novel data set on the German book market we find that between 26 and 55% of the decrease in book sales from 2014-2017 can be explained by the decrease in the number of bookstores. This indicates that brick-and-mortar stores and e-Commerce are imperfect substitutes. One explanation could be that some consumers prefer to purchase books offine because of the service provision in brick-and-mortar stores (e.g., advice, atmosphere, presentation, sales-effort, etc.). We also find that the degree of substitutability differs between different types of books. When a bookshop closes the decrease in sales of fiction titles is more than 2 times larger than the decrease in sales of non-fiction titles. Our findings indicate that regulatory measures and vertical restraints that increase the number of bookstores can have a positive effect on the demand for books even in the presence of e-Commerce.
Keywords: 330; Experience goods; Retailing; e-Commerce